Pengaruh Komposisi Media Tanam dan Ukuran Polybag Terhadap Pertumbuhan dan Hasil Tomat (Licopercicum escelentum Mill) - Florentina Bui; Maria Afnita Lelang; Roberto I. C. O. Taolin (Savana Cendana, 2016)
This study aims to determine the effect and prove the composition of planting media and polybag size that can provide the best growth and yield of tomato. The design used was factorial randomized block design with three replications. The first factor is the composition of planting medium which is a mixture of soil, husk charcoal and manure consisting of three levels namely 1: 2: 3, 2: 1: 3 and 3: 2: 1. The second factor is a polybag size consisting of three levels namely 15 x 20 cm, 20 x 20 cm and 20 x 25 cm. The results showed that interaction between planting media composition and polybag size only occurred at plant height 14 DAP and fruit weight per plant of harvest III. The composition of planting medium has a significant effect on stem diameter 28 DAP and 42 DAP, fruit weight per plant of harvest I, harvest II and harvest III, the fresh and dry weight of stover. While the size of polybag significantly affect the soil temperature at each observation time, plant height 14 HST and 28 HST, stem diameter 28 HST, leaf area, weight per fruit, number of fruits per plant, fruit weight per plant harvest I, harvest II, harvest III and total harvest, fresh weight and dried fruits and dry weight of the roots. While the size of polybag significantly affect the soil temperature at each observation time, plant height 14 HST and 28 HST, stem diameter 28 HST, leaf area, weight per fruit, number of fruits per plant, fruit weight per plant harvest I, harvest II, harvest III and total harvest, fresh and dry weight of stover and dry weight of roots. Planting media with a 1: 2: 3 composition yields the highest total yield per crop of 964.5 g compared to 2: 1: 3 and 3: 2: 1. The use of polybags with a size of 20 x 25 gives the highest total yield per plant of 1,022.7 g compared to 15 x 20 and 20 x 20.